PENGARUH MOTIVASI DAN KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMK BERYAYASAN BUDDHIS SE-TANGERANG - Oey Hannes Widjaya; Inggrid Suryatenggara; Lianah The (Jurnal Serina Ekonomi dan Bisnis, 2023)
The purpose of this research was to test empirically the ef ect of learning motivation, emotionalintelligence, learning motivation and emotional intelligence simultaneously on the Mathematical learningoutcome of Buddhist-based vocational high school students in Tangerang Raya. This study uses quantitativemethods, with the sample size was determined using the Slovin formula and obtained a sample of 210, 11th grade students of the Buddhist Foundation Vocational School in Tangerang Raya. Test the validity of theinstrument using Pearson Product Moment and test the reliability using Alpha Cronbach. Data analysisused multiple linear regression. The results showed that learning motivation and emotional intelligence hada significant ef ect on mathematics learning outcome for class XI SMK students as evidenced by asignificance value of 0.000<0.05. Learning motivation and emotional intelligence simultaneously af ect themathematics learning outcome of class XI SMK students as evidenced by a significance value of 0.000 <0.05.